A Study on Yogic and Martial arts Training's impact on Students' Focus (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Overall, martial arts training is beneficial because it promotes self-control, physical and mental health, and respect for others. Incorporating yoga into training may be beneficial for athletes since it helps them focus better, get in the proper mindset for competition, and learn to control their emotions. The goal of this study was to look at how student instructors' memory changed after four weeks of yoga classes. The Multifactorial Memory Questionnaire (MMQ) was used as a demographic questionnaire in this experimental investigation. A total of thirty female student instructors from colleges of education were randomly assigned to one of two groups: the experimental group and the control group. For 30 minutes each day, for 30 days, the experimental group practiced Padmasana and Paschimottanasana as part of their everyday yoga routine. At the end of the one-month trial, both groups were re-evaluated.